Religious and national dialogue in Hamzanwadi’s Wasiat Renungan Massa: A hermeneutical perspective - Herman, Herman Wijaya; Andayani; Wardani, Nugraheni Eko (Research Journal in Advanced Humanities, 2024)
This article conducts an in-depth analysis of the dialogue between religion and nationality in Hamzanwadi's mass devotional writings using Gadamer's hermeneutic approach. The results revealed the complexity of the interaction and the implications of these two aspects in cultural and religious contexts. Religion plays a central role in shaping deep moral foundations, whereas nationality becomes a collective identity closely linked to religious values. The main findings highlight that religion and nationality influence each other in the formation of people's identities, moralities, and values. This study provides a deeper understanding of how religion and nationality interact positively, promoting tolerance, diversity, and inclusiveness within the framework of religion and nationality. The results of this study have important implications for understanding the role of religion and nationality in shaping a strong social and moral unity. This article outlines these findings and provides deep insights into the contribution of religion and nationality in shaping people's identity and morality.